Proceso de atención de enfermería en paciente con enfermedad pulmonar obstructiva crónica (Epoc) en adulto mayor - Ovaco Rodríguez, Alba Cecilia (2018)
Chronic obstructive pulmonary disease is a problem that is affecting worldwide. Extensive studies report that usually between 10% and 20% of adult males in the general population meet the diagnostic criteria of chronic bronchitis. The disease is much more frequent among smokers, both men and women. It is said that they present chronic bronchitis and pulmonary emphysema, this pathology presents with the following symptoms: dyspnea, cough with expectoration. For the diagnosis of this pathology is going to perform a chest x-ray, spirometry, arterial blood gas, blood count and smear microscopy. The risk factors that makes the person get the disease, is the consumption of cigarettes, untreated respiratory infections, genetic factors, or be exposed to chemical gases. The taxonomy that was carried out in this clinical case is that of Nanda, Nic, Noc, where we will perform a physical assessment and by pattern, where we seek the recovery of the patient applying nursing interventions. As a general objective we have to determine the importance of the process of nursing care in the care of patients with chronic obstructive pulmonary disease. An 86-year-old male patient entered the emergency area due to presenting, dyspnea, chest pain, and cough with expectoration, diaphoresis, and asthenia. Hyperthermic patient reported feeling weak. The treatment that is applied is oxygen therapy, the administration of drugs such as bronchodilators, anticholinergics, antibiotics; by means of this the patient is able to reduce his symptomatology. Using Virginia Henderson's theory, the patient care model, which is based on patient needs, promotes patient and family care.